Título Padrão - LEAL, Abniza Pontes de Barros; ZAVAM, Aurea Suely (Revista de Letras, 2022)
The contemporary language practices are becoming increasingly more multisemiotic resulting in a real explosion of new texts and genres which start to dominate the mediatic practices. It is up to the school “not only to critically contemplate these new language and production practices, but also to foster debate and other social demands that surround these practices and its uses (BNCC, 2018, p. 68). From this perspective, which considers the text as the center of study, we understand that it is up to the teachers, especially the ones of Portuguese language, to guide their students towards the: recognition of different speeches; variations of the interdiscursive game dictated by different contexts; concept of enunciation; and understanding the meaning of discursive practices and discursive formation. This study seeks to accomplish the following general objective: analyze the interdiscursivity in utterances constructed by memes about events experienced in recent months by Brazilian society. We intend to answer the following question: how to reconstruct the socio-historical scenario with which we interact taking into consideration the intersections of everyday speeches? We carried out a qualitative investigation based on the theoretical references of Maingueneau (1997, 2005, 2006, 2012) and reached the conclusion that there is a wide space for the understanding of interdiscourse related to memes’ ludic function. Keywords: Interdiscourse. Meme. Teaching.